Enhanced piezoelectric and acoustic performances of poly(vinylidene fluoride-trifluoroethylene) films for hydroacoustic applications. Issue 10 (27th February 2020) - Zhou, Zhenji; Li, Jinglei; Xia, Weimin; Zhu, Xuan; Sun, Tao; Cao, Congjun; Zhang, Lin
Abstract : Concerning the study of flexible piezoelectric devices, P(VDF-TrFE) shows more merits than OPVDF in piezoelectric and acoustic performances for hydroacoustic applications. Abstract : Concerning the study of flexible piezoelectric devices, both scholars and engineers propose that poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) shows more merits than oriented polyvinylidene fluoride (OPVDF) in terms of dielectric, piezoelectric, mechanic–electric, acoustic emission reception performances, etc. Thus, in this study, to clarify the differences between the two types of polymers on their ferroelectric and piezoelectric behaviors, we systematically investigated samples to analyze their molecular structures and phase structures, and to compare their dielectric properties and acoustic emission reception performances. It was found that the wedge effect of TrFE, P(VDF-TrFE), possesses higher regular β phase crystal grains, which are easier to order along the electric field and possess more ordered static charge distribution than that of OPVDF. Consequently, a considerable saturated electric polarization ( P m ∼ 15 μC cm −2 under 225 MV m −1 ), a large piezoelectric coefficient ( d 33 ∼ −21.5 pC N −1 ) and a low coercive electric field ( E c ∼ 50 MV m −1 ) were obtained in the P(VDF-TrFE) films. It is worth noting that P(VDF-TrFE) shows a more stable d33 piezoelectric response (up to 120 °C) than that of the OPVDF. Additionally, the P(VDF-TrFE) piezoelectric films exhibit a sensitive acoustic emission reception property at approximately 70 dB and an extensive response frequency range from 10 to 100 kHz. These combined properties demonstrate that P(VDF-TrFE) piezoelectric films are a promising material for flexible and easily shaped electronic devices, including hydroacoustic sensors, actuators, and energy transfer units.